A prospective study of body size during childhood and early adulthood and the incidence of endometriosis - Vitonis, Allison F. (Oxford University Press, 2010)
BACKGROUND: An inverse association between adult body mass index (BMI) and risk of endometriosis has frequently been reported. However, the association between body size during childhood and early adulthood and endometriosis is not as well documented. METHODS: Using data collected from the Nurses' Health Study II, a prospective cohort study of premenopausal US nurses, that began in 1989, we have attempted to clarify this relationship. Data are updated every 2 years with follow-up for these analyses through 2001. In 1989 women recalled their body size at ages 5, 10 and 20 years using a validated 9-level figure drawing. RESULTS: During 831 910 person-years of follow-up, 1817 cases of self-reported laparoscopically-confirmed endometriosis were observed among women with no past infertility. After adjusting for age, birthweight, age at menarche, parity, oral contraceptive use and adult BMI, we observed a significant reduction in the incidence of endometriosis with increasing body size for all time periods. The relative risks (RRs) comparing the smallest and largest figure sizes to the middle category during childhood (ages 5–10) were 1.18 (95% confidence interval 1.02–1.36) and 0.82 (0.66–1.02), P-trend = 0.0002. At age 20, the RRs for the same comparisons were 1.32 (1.06–1.65) and 0.87 (0.74–1.03), P-trend = 0.04. Additional adjustment by menstrual cycle length and regularity yielded similar associations. The associations were stronger among nulliparous women than among parous women, although not all differences were statistically significant. CONCLUSION: In this large cohort of premenopausal women, there was evidence of a persistent inverse association between childhood and early adulthood body size and incidence of laparoscopically confirmed endometriosis, independent of adult BMI and menstrual cycle characteristics.